Future needs for ERCP: incidence of conditions leading to bile duct obstruction and requirements for diagnostic and therapeutic biliary procedures. Issue 10 (October 1990) - Gear, M W; Dent, N A; Colin-Jones, D G; Lennard-Jones, J H; Colley, J R
Abstract : Although the development of endoscopic methods of treatment for biliary obstruction has proceeded rapidly in recent years, endoscopic retrograde cholangiopancreatographic (ERCP) services are patchily distributed. A recent survey by the British Society of Gastroenterology has shown that almost half the district general hospitals questioned did not have a sphincterotomy service available locally. To assess the level of provision required, two investigations have been undertaken. Firstly, an epidemiological study of bile duct obstruction has been carried out in the South Western Region. Secondly, the actual surgical and endoscopic workload in treating obstructive jaundice has been analysed in two health districts. Using present incidence and treatment rates at least 50 ERCPs per 100, 000 of the population per year are estimated to be required in the future. Surgical treatment rates can be expected to fall as the number of therapeutic ERCPs increases. The implications of this estimate in equipment and staffing terms are discussed.